EXPLORASI DAN MUTU BERAS GENOTIP PADI MERAH DI KABUPATEN PASAMAN BARAT SUMATERA BARAT - Anhar, Azwir (IAIN Batusangkar, 2013)
The purpose of this study was to determine the nutrient content based on the phenotype of red rice in West Sumatra West Pasaman. The study was conducted in the West Pasaman by doing a survey to determine and collect the red rice in the area. Limited access to isolated areas growing regions in the rice collection was also done by buying rice from the traditional market vendors West Pasaman. Analysis of the nutrient content in the form of protein and amylose conducted in the Laboratory of Chemistry Department of Chemistry, State University of Padang. The results showed that in the West Pasaman found 5 red paddy rice genotypes. Amylose content ranged from 27.16% to 40.13% Island Manggis until at Nabara. Protein content ranged from 5.93% to 8.72 on the genotype Nabara Cimarisik genotype. Based on these results it can be concluded that the Dolok Nabara (8.25%) and Cimarisik (8.72%) developed considering the potential for relatively higher protein content than rice genotypes grown in West Sumatra. In conclusion, the amylose content of the five genotypes were high.Key words: explorasi, genotip, quality rice, red rice, west pasaman